Motivasi Petani Dalam Mengelola Hutan Rakyat Di Desa Sukoharjo 1 Kecamatan Sukoharjo Kabupaten Pringsewu - Insani Fahma Nurdina; Asihing Kustanti; Rudi Hilmanto (Jurnal Sylva Lestari, 2015)
Lampung Province is one province in Indonesia has deforestation for about 600 hactare in a year (Pusdaling, 2013). This leads to the decline of the quality and quantity of forest. That condition is inversely of Sukoharjo 1 Village Sukoharjo District Pringsewu Regency, the development in that village more than 200 hectar through the private forest development. The purpose of this research were to know the level of motivation farmers and the factors that influence the motivation farmers in managing private forest. The research was conducted on November 2014 in Sukoharjo 1 Village, Sukoharjo District Pringsewu Regency. The population in this research were the group of Ngudi Rukun with the number of 32 farmers, the method sampling of this research used census. Analysis method which used in this research was descriptive quantitative, it aimed to know the level of farmers' motivation by using the technique of determining likert, while to know the factors of influenced with the level of farmers' motivation in managing forest community used ordinal regression test. Based on the research's result, it can be known that farmers' motivation are in high category (53,15%). The factors which influenced farmers' motivation were age, revenue, farm experience, education, and the activities of farmer groups, extension activities and access of the information. Keywords: private forest management, farmer motivation